Afmeting excl. passe-partout. . Titel prent: Hinder. . Personen v.l.n.r.: ?, Kuyper, de Savornin Lohman - Hahn, Albert
Afmeting excl. passe-partout. Titel prent: Hinder. Personen v.l.n.r.: ?, Kuyper, de Savornin Lohman.